Functional programming projects with JavaScript. (Pearson, 2023)
3.5 Hours of Video Instruction In learning and following the core concepts of Functional Programming, you can quickly write more maintainable, flexible, and beautiful code. Description Functional Programming is a revolutionary way of writing code and is rapidly gaining traction in the world of software development. While Object-Oriented Programming is still the most popular programming paradigm, there are a number of problems that come about when using it - hard-to-find bugs, tightly coupled code, very difficult to scale. Functional programming allows us to solve or avoid all these problems by taking a very different approach to writing software. Learn all about the core concepts of Functional Programming and how to apply them in JavaScript, mix of screen casting, slides, and coding. Basic functional concepts lead to first class functions, which leads to working with arrays and objects and then advanced functional concepts. Related Learning: Watch and learn from Shaun's other videos: Learn JavaScript Learn to Program with JavaScript About the Instructor Shaun is a Senior Software Developer who specializes in Full-stack development and Software Architecture. He manages teams of developers, as well as teaches many hundreds of thousands more how to create enterprise-ready applications. Shaun's online courses have over 300,000 learners largely because of his passion for development and his focus on helping people apply their programming skills in the real world. He is a life-long programmer and problem-solving addict whose goal is to help people solve meaningful problems by mastering the art of software development. Please don't hesitate to get in touch with him about any opportunities or if you'd like to stay up to date on his other courses and live trainings. Skill Level Beginner to Intermediate What You Will Learn The core concepts of Functional Programming and how to apply them in Javascript First-class functions and what we can do with them JavaScript's built-in array functions and how they help us work with data Advanced functional concepts such as currying, recursion, and composition Who Should Take This Course Job titles: Software developer Programmer Course Requirements Pre-requ's: Knowledge of JScript syntax. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Prentice Hall, Sams, and Que. Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.